Ecological Citizenship: Bioconversion of Food Wastage With Maggot Black Soldier Fly - Mufidah, Nastiti; Pertiwi, Faninda Novika; Negara, Tirta Dimas Wahyu; Jehyeh, Nureeman (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
This study aims to analyze the formation of ecological citizenship to overcome the problem of food wastage through the bioconversion of Black Soldier Fly maggots. The method used is a qualitative case study with observation, interview, and documentation data collection techniques, using triangulation analysis techniques. This study was conducted on three groups of informants: chicken noodle shops, fruit shops, and households in Ponorogo. The informants in this study were specifically informants who initially threw their waste directly into the trash and ended up in the Final Disposal Site, so that it became one with inorganic waste without further treatment. The results of the study show that the embodiment of the ecological citizenship model put forward by Dobson, namely anthropocentrism, is a reference for the analysis of ecological citizenship about the relationship between individuals who occupy the same ecological space determined by their ecological footprint, so that it can be an alternative if managed and used correctly with the proper handling techniques. The conclusion of this study shows that the obligation of ecological citizenship imposed on each individual can be realized through the processing of food waste produced by bioconversion using BSF maggots.